2013
DOI: 10.1111/dom.12081
|View full text |Cite
|
Sign up to set email alerts
|

A Phase IIb, randomized, placebo‐controlled study of the SGLT2 inhibitor empagliflozin in patients with type 2 diabetes

Abstract: In patients with type 2 diabetes, empagliflozin resulted in dose-dependent, clinically meaningful reductions in HbA1c and FPG, and reductions in body weight compared with placebo. Empagliflozin was well-tolerated with a favourable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
174
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(195 citation statements)
references
References 15 publications
17
174
0
4
Order By: Relevance
“…The large placebo-controlled 24-week study by Roden and colleagues 4 confirms these favourable effects with empagliflozin 10 and 25 mg compared to placebo in patients treated with diet alone, and reproduces results of a previous smaller and shorter trial 5 . Adverse events are those expected from this new pharmacological class, with a slightly increased incidence of genital and benign urinary infections 3 .…”
supporting
confidence: 62%
“…The large placebo-controlled 24-week study by Roden and colleagues 4 confirms these favourable effects with empagliflozin 10 and 25 mg compared to placebo in patients treated with diet alone, and reproduces results of a previous smaller and shorter trial 5 . Adverse events are those expected from this new pharmacological class, with a slightly increased incidence of genital and benign urinary infections 3 .…”
supporting
confidence: 62%
“…Data were sorted by first author, year of publication, country of the study, design, age range of the participants, total sample size, SGLT2 inhibitor, comparator, number of patients, dosage, and follow‐up duration (Table 1). 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55 …”
Section: Methodsmentioning
confidence: 99%
“…It has been found that surrogate markers of beta cell function including homeostasis model assessment-β were also improved. In addition, a modest but a signifi cant decrease in body weight has also been noted, 7 and studies have also confi rmed that the weight reduction was due to decreased body fat rather than due to dehydration, and was explained by loss of glucose via the kidney. 8 The glucosuria that occurs due to SGLT inhibition is accompanied by mild diuresis which contributes to an additional benefi t of a sustained and moderate reduction in blood pressure (BP).…”
Section: Mechanism Of Actionmentioning
confidence: 94%